1998
DOI: 10.1046/j.1525-1497.1998.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histamine-2 receptor antagonists on blood alcohol levels

Abstract: OBJECTIVE:To determine the effect, if any, of histamine type 2 receptor antagonists (H 2 RAs) on serum alcohol levels under various conditions including type of H 2 RA receptor antagonist, alcohol dose, and fed status of the subject. STUDY DESIGN:Meta-analysis of the published literature.DATA SOURCES: Studies were identified by MEDLINE (January 1982 through December 1997) using the key words H 2 receptor antagonists and alcohol. Other studies were identified by reviewing bibliographies of retrieved articles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Central nervous system agents were the most common medications (59.1% mainly opioids and psychotherapeutic agents, including antidepressants; Neuman et al, 2006). There is a potential interaction between alcohol and H2 receptor antagonists such as cimetidine (Weinberg et al, 1998). The inhibition of the metabolism of acetaldehyde may cause disulfiram-like reactions.…”
mentioning
confidence: 99%
“…Central nervous system agents were the most common medications (59.1% mainly opioids and psychotherapeutic agents, including antidepressants; Neuman et al, 2006). There is a potential interaction between alcohol and H2 receptor antagonists such as cimetidine (Weinberg et al, 1998). The inhibition of the metabolism of acetaldehyde may cause disulfiram-like reactions.…”
mentioning
confidence: 99%
“…Cimetidine and ranitidine, which are H 2 RA, can increase the peak levels of alcohol and the area under the alcohol concentration curve (DiPadova et al, 1992). It was subsequently determined that the resulting elevations in blood alcohol levels were unlikely to exceed legal limits or be clinically relevant in individuals with adequate nutrition and with moderate social alcohol consumption (Raufman et al, 1993;Weinberg et al, 1998). A recent in vitro study and computer simulation confirmed that cimetidine can act either as a competitive or a non-competitive inhibitor, depending on the class of ADH isozyme.…”
Section: Alcohol and Histamine H 2 Receptor Antagonistsmentioning
confidence: 99%
“…9 In addition, alcohol can affect the pharmacokinetics of drugs by delaying gastric emptying time and inducing enzyme cytochrome p450 CY2E1 in the liver. For example, it is well known that some antibiotics such as metronidazole, cephamandole, cefoperazone, griseofulvin, and procarbazine can cause disulfiram-like reactions by inhibiting metabolism of acetaldehyde.…”
Section: Iatrogenic Alcohol In Medicationmentioning
confidence: 99%
“…8 H 2 receptor antagonists such as ranitidine inhibit gastric ADH (alcohol dehydrogenase), and it is possible that coadministration of alcohol and H 2 receptor antagonists may cause unexpectedly high blood alcohol concentrations. 9 In addition, alcohol can affect the pharmacokinetics of drugs by delaying gastric emptying time and inducing enzyme cytochrome p450 CY2E1 in the liver. 8 Inducing cytochrome p450 CY2E1 affects var-ious compounds such as acetaminophen, which can be metabolized to toxic compounds and cause liver toxicity.…”
Section: Iatrogenic Alcohol In Medicationmentioning
confidence: 99%